(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate pain reduction and clinical improvement of oral lichen planus lesions treated with triamcinolone acetonide 0,1% ointment. Subject and method: A case series study was conducted on 12 symptomatic patients with oral lichen planus at the Department of Odonto-Stomatology Clinic, University of Medicine and Pharmacy at Ho Chi Minh City, and the Outpatient Department, National Hospital of Odonto-Stomatology, Ho Chi Minh City. Patients were treated with triamcinolone acetonide 0,1% ointment applied three times daily for 28 days. Pain intensity was assessed using the visual analogue scale (VAS), and lesion severity was evaluated using the REU scoring system at three time points: baseline (T0), day 14 (T1), and day 28 (T2). Results: At baseline, 75% of patients reported severe pain (VAS 7–10). Mean VAS scores decreased by 22% at T1 and 50% at T2. Preliminary results suggest that the mean REU scores decreased by 20% after two weeks and 33% after four weeks of treatment. Ulcerative lesions tended to exhibit the earliest and most marked improvement, while atrophic lesions improved gradually. Keratotic lesions showed minimal change. Severe lesions and patients with systemic comorbidities demonstrated poorer treatment response. Conclusion: Triamcinolone acetonide 0,1% ointment is effective in reducing pain and improving lesion severity in patients with mild to moderate oral lichen planus.